Effectiveness of Online Seminar to Increase Knowledge and Interest of Poltekkes Putra Indonesia Malang’s Students Towards Halal Pharmacy - Maulina, Novia; Fitriyani, Fitriyani; Al Bustomi, Mochammad Yazid; Permatasari, Anggraini Intan; Arriziq, Muhammad Abbas (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2025)
To augment awareness of halal pharmaceuticals, there is a need for proactive efforts, such as conducting promotional activities like seminars that delve into various issues related to the concept of halal in the formulation and selection of pharmaceutical products. The objective of this research was to discern the impact of an online seminar on enhancing the knowledge and interest of vocational students at Poltekkes Putra Indonesia Malang in the realm of halal pharmacy. Employing a quantitative approach, an experimental design was utilized with one group pre and post-test, incorporating active and participatory learning methods. Statistical analysis utilized the Wilcoxon sign rank test, focusing on 49 participants of the online seminar who were vocational students at Poltekkes Putra Indonesia Malang. The study revealed a participant demographic of 10 males (20%) and 39 females (80%), with ages ranging from 18 to 22 years. The analysis of knowledge levels indicated a significant increase from 35% to 63%, categorizing participants as having good knowledge of halal pharmacy. The statistical test, employing the Wilcoxon sign rank test, yielded a p-value of 0.001 ≤α (0.05), signifying an increase in interest among Poltekkes Putra Indonesia students regarding halal pharmacy, with 63% expressing strong interest and 39% indicating moderate interest. In conclusion, the online seminar on halal pharmacy at Poltekkes Putra Indonesia Malang effectively enhanced the knowledge of participating students.